Do something else : the road ahead for the mainline church - Phillips, Nate (Nathaniel David) (Wipf and Stock Publishers, 2016)
Do Something Else is meant to encourage faith communities and their leaders to reconsider ""church as usual, "" reengage Spirit-led entrepreneurialism, and reimagine new models of ministry bubbling up in their midst. Many churches and leaders are already setting the pace. They are establishing new gatherings in old buildings and using new building to do old things. They are emphasizing diversity, welcome, and friendship. If these stories are hidden from view, they shouldn't be. These pages will uncover how new expressions get started, how they are led, how they struggle, and how they are sustain.